Pengaruh Motivasi Berprestasi terhadap Social Loafing pada Mahasiswa Psikologi Universitas X - Alifah Desita Jannah; Agitia Kurnia Asrila (Lembaga Yasin AlSys, 2026)
Social loafing is the tendency of individuals to reduce their effort when working in groups, which can hinder the effectiveness of learning in higher education and is a particular concern in the context of academic group work among university students. This study aimed to examine the effect of achievement motivation on social loafing among students of the Psychology Study Program at Universitas Negeri Padang. A quantitative approach with a correlational design was employed. Data were collected using Likert-scale instruments to measure achievement motivation and social loafing in 88 active psychology students selected through purposive sampling. The data were analyzed using linear regression. The results showed a significant effect of achievement motivation on social loafing (r = 0.79; p = 0.008 < 0.05), indicating that the higher students’ achievement motivation, the lower their tendency to engage in social loafing in academic group work. The study concludes that achievement motivation plays an important role in minimizing social loafing among students and therefore needs to be taken into account in the design of group-work-based learning interventions in higher education.